1997
DOI: 10.1007/s002130050201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the selective serotonin reuptake inhibitor fluvoxamine on CCK-4 induced panic attacks

Abstract: Data from animal studies suggest a functional relationship between the cholecystokinin-ergic (CCK) and the serotonergic (5-HT) system. There is increasing evidence that the cholecystokinin-4 (CCK4) challenge test could be a valid experimental model for panic attacks in man. The aim of the present study is twofold; 1) to validate this model further and 2) to shed more light on the putative CCK/5-HT interaction. To this end, we studied the effect of the selective serotonin reuptake inhibitor (SSRI) fluvoxamine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 35 publications
4
26
2
Order By: Relevance
“…The CCK-4-induced panic rate dropped significantly from 76% to 29% within eight weeks of treatment in the fluvoxamine group, whereas there was only a nonsignificant decrease from 67% to 56% in the placebo group. In contrast to treatment with imipramine or fluvoxamine (Bradwejn and Koszycki 1994b;van Megen et al 1997), we found no statistically significant effect of vigabatrin on the physiological response to CCK-4 such as heart rate.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…The CCK-4-induced panic rate dropped significantly from 76% to 29% within eight weeks of treatment in the fluvoxamine group, whereas there was only a nonsignificant decrease from 67% to 56% in the placebo group. In contrast to treatment with imipramine or fluvoxamine (Bradwejn and Koszycki 1994b;van Megen et al 1997), we found no statistically significant effect of vigabatrin on the physiological response to CCK-4 such as heart rate.…”
Section: Discussioncontrasting
confidence: 93%
“…Although it has to be considered that our study was not placebo-controlled and a certain placebo effect cannot be ruled out, the pronounced anxiolytic effects of vigabatrin are unlikely to be merely caused by a placebo effect. Previous studies investigating the effects of fluvoxamine on CCK-4-induced panic in a placebo-controlled study revealed a marked effect of fluvoxamine on CCK-4-induced panic in view of a slight and non-significant effect in the placebo group (van Megen et al 1997). The CCK-4-induced panic rate dropped significantly from 76% to 29% within eight weeks of treatment in the fluvoxamine group, whereas there was only a nonsignificant decrease from 67% to 56% in the placebo group.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Studies so far have shown that treatment with SSRIs significantly decreased the sensitivity of patients with PD to the panicogenic effects of CCK-4, flumazenil, and CO 2 (Bell et al, 2002;Bertani et al, 1997;Perna et al, 1997;Shlik et al, 1997;van Megen et al, 1997). These results support the view that 5-HT-ergic enhancement by SSRIs leads to antipanic effects.…”
Section: Effects Of Treatment On Panic Challengementioning
confidence: 60%
“…Criterium seven, i.e., drugs which are clinically ineffective in panic disorder are unable to block CCK-4 induced attacks, has been studied only in healthy volunteers (de Montigny 1989;. Like sodium lactate-and CO 2 -induced panic, CCK-4-induced attacks are blocked by antipanic treatment with antidepressants van Megen et al 1997;Shlik et al 1997) or benzodiazepines (de Montigny 1989. Although CCK antagonists have so far failed to be effective in the treatment of panic disorder (Kramer et al 1995) or benzodiazepine withdrawal induced anxiety (Abelson et al 1995), CCK-4 induced attacks are a promising strategy to elucidate the neurobiological correlates of panic disorder.…”
Section: Discussionmentioning
confidence: 99%